I'm new to logic, and I'm really confused about the fell swoop method. I have to determine the validity of $$((P \lor Q) \land (\lnot P \land \lnot Q)) \to \lnot P)$$ using the fell swoop method. So far, I have managed to come up with this. I'm thinking that the formula is valid, but I'm having trouble illustrating this properly. I hope someone can correct and guide me please. Thanks

fell swoop table

  • 4
    $\begingroup$ What is the fell swoop method? Google didn't give me anything. $\endgroup$ Nov 26, 2019 at 9:45
  • $\begingroup$ @ThomasAhle I just found some vague Quine references, related to logic, but I don't know either. $\endgroup$ Nov 26, 2019 at 9:46
  • $\begingroup$ The expression can be simplified to $\neg P \lor Q$. Therefore, it does not hold for $P \land \neg Q$. $\endgroup$ Nov 26, 2019 at 9:54
  • $\begingroup$ @MauroALLEGRANZA I noticed. They're the same now I think. $\endgroup$ Nov 26, 2019 at 9:58
  • $\begingroup$ Never heard of "fell swoop" in this context. Did you translate from another language? $\endgroup$
    – AlvinL
    Nov 26, 2019 at 9:59

1 Answer 1


The "fell swoop" method (see WVO Quine, Methods of Logic (4th ed., 1982))is a method of "fast checking" that can be used to verify (in an important range of cases, also if it is not valid in general) if a formula is satisfiable or falsifiable.

In a nutshell, it amounts to build a single (suitably chosen) row of the truth table for the formula to be checked.

Regarding the example :

$[(P∨Q) ∧ (¬P ∧ ¬Q)] → ¬P$,

the method try to check if the formula is not valid.

Being the main connective the conditional, this can happen only if the antecedent is TRUE and the consequent is FALSE.

Thus, we start with a valuation $v$ such that $v(¬P)= \text F$, i.e. $v(P)= \text T$.

This is enough to have $v(P∨Q)= \text T$.

Regarding $(¬P ∧ ¬Q)$, we have that $v(¬P)= \text F$ implies : $v(¬P ∧ ¬Q))= \text F$.

Thus $v([(P∨Q) ∧ (¬P ∧ ¬Q)]= \text T \land \text F = \text F$.

In conclusion : we have shown that if the consequent is FALSE also the antecedent must be, i.e. that it is impossible that the antecedent is TRUE and the consequent is FALSE, and this means that the formula is valid.

The method works when the main connective is a conditional because in the truth table for the conditional there is only one row that falsifies the formula.


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .